Minimal recovery time needed to return to social engagement following nasolabial fold correction with hyaluronic acid fillers produced with XpresHAn technology - Swift A; von Grote E; Jonas B; Nogueira A (Dove Medical Press, 2017)
Arthur Swift,1 Erika von Grote,2 Brandie Jonas,2 Alessandra Nogueira2 1Arthur Swift Research Inc., Montreal, QC, Canada; 2Medical Affairs, Galderma Laboratories, L.P., Fort Worth, TX, USA Introduction: The appeal of hyaluronic acid fillers for facial soft tissue augmentation is attributable to both an immediate aesthetic effect and relatively short recovery time. Although recovery time is an important posttreatment variable, as it impacts comfort with appearance and perceived treatment benefit, it is not routinely evaluated. Natural-looking aesthetic outcomes are also a primary concern for many patients.Materials and methods: A single-center, noncomparative study evaluated the time (in hours) until subjects return to social engagement (RtSE) following correction of moderate and severe nasolabial folds (NLFs) with RR (Restylane® Refyne) and RD (Restylane® Defyne), respectively. Twenty subjects (aged 35–57 years) who received bilateral NLF correction documented their RtSE and injection-related events posttreatment. Treatment efficacy was evaluated by improvements in Wrinkle Severity Rating Scale (WSRS) and subject satisfaction questionnaire at days 14 and 30, and by Global Aesthetic Improvement Scale (GAIS) at day 30. Safety was evaluated by injection-related events and treatment-emergent adverse events.Results: Fifty percent of subjects reported RtSE within 2 hours posttreatment. WSRS for the RR group improved significantly from baseline at day 14 (–1.45±0.42) and day 30 (–1.68±0.46) (P<0.001), respectively. WSRS for the RD group improved significantly from baseline at day 14 (–2.22±0.44) and day 30 (–2.50±0.50) (P<0.004), respectively. All GAIS improvements were clinically significant at day 30. The majority of injection-related events were mild or moderate. Two subjects experienced 3 related treatment-emergent adverse events; 1 RR subject experienced severe bruising, and 1 RD subject experienced severe erythema and mild telangiectasia. Subject satisfaction was high regarding aesthetic outcomes and natural-looking results.Conclusion: Optimal correction of moderate NLFs with RR and severe NLFs with RD involved minimal time to RtSE for most subjects. Treatments that significantly improved WSRS and GAIS, were generally well-tolerated, and provided natural-looking aesthetic outcomes. Keywords: hyaluronic acid, dermal filler, nasolabial fold, recovery time, naturalness